Performance and Carcass Characteristics of Broiler Chickens Fed Diets Containing Whole Grains of Gayamba Pearl Millet (Pennisetum glaucum) - Kawu, Y. U.; Ibrahim, A.; Doma, U. D. (Nigerian Journal of Animal Science and Technology (NJAST), 2020)
A Study was carried out to investigate the growth performance and carcass characteristics of broiler chickens fed diets containing graded levels of whole gayamba pearl millet (WGGM). Five diets were formulated in which WGGM replaced milled gayamba millet (MGM) at 0, 5, 10, 15 and 20% levels, coded as diets 1, 2, 3, 4 and 5 respectively. A total of three hundred and fifty broiler chicks were randomly allotted to five diets in a completely randomized design. Each treatment consists of 70 chicks and replicated five times to contain 14 birds each. Feed and water were provided ad libitum throughout the experimental period which lasted for 49 days. Results of productive performance revealed that final weights were higher (P<0.05) on diets 2, 3 and 1. A similar trend was also observed for total weight gain. Significant (P<0.05) differences were also observed for overall daily weight gain (DWG) and feed conversion ratio (FCR). Daily weight gain was significantly (P<0.05) higher in birds fed diets 1 (35.83g), 2 (36.27g) and 3 (36.36g) than the values of 30.91 and 32.78g obtained on diets 5 and 4 respectively. Feed conversion ratio was also better in birds fed diets 1 (2.20), 2 (2.23) and 3 (2.18) and poorer on diets 4 and 5 with a value of 2.51 each. Carcass characteristics revealed a significant (P<0.05) influence of diet on carcass weight and dressing percentage in favour of diets 1, 2 and 3, while relative weights of proventriculus and gizzard were higher on diets 4 and 5. Abdominal fat weight was highest (P<0.05) in birds fed diet 5 and lowest on diet 4. It was therefore concluded that whole gayamba millet can replace the milled form at up to 10% level in broiler chicken diets without compromising growth performance and carcass yield.